2009
DOI: 10.1021/tx800378z
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Interacts with Selenite and Attenuates Selenite-Induced Cataractogenesis

Abstract: Selenite, the most commonly encountered toxic form of selenium, in overdose, is used to induce cataracts in rats. This study demonstrated that selenite, but not selenate, would interact with the carotenoid astaxanthin (ASTX), as determined using isothermal titration calorimetry and NMR. The maximum absorption of ASTX decreased with increasing selenite concentration, indicating that the conjugated system of ASTX was changed by selenite. Such interactions between ASTX and selenite were also supported by the atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…This prevention may not be due to an anti-oxidant activity of AST but be due to a direct interaction of AST with selenite. 39 In the present study, administration of AST to a chick embryo model of steroid-induced cataract resulted in a significant suppression of HC-induced lens opacity. Furthermore, treatment with AST also significantly suppressed reduction of the lens glutathione level, suggesting that the effect of AST in suppressing lens opacity involved reduction of oxidative stress.…”
Section: Discussionsupporting
confidence: 47%
“…This prevention may not be due to an anti-oxidant activity of AST but be due to a direct interaction of AST with selenite. 39 In the present study, administration of AST to a chick embryo model of steroid-induced cataract resulted in a significant suppression of HC-induced lens opacity. Furthermore, treatment with AST also significantly suppressed reduction of the lens glutathione level, suggesting that the effect of AST in suppressing lens opacity involved reduction of oxidative stress.…”
Section: Discussionsupporting
confidence: 47%
“…Liao et al [115] reported that astaxanthin could interact with selenite, whose accumulation in the lens might cause cataract formation directly, and thus could delay seleniteinduced lens crystalline precipitation and attenuate seleniteinduced cataractogenesis in rats. Nakajima et al [116] found that astaxanthin had neuroprotective effects against retinal ganglion cell damage.…”
Section: Ocular Protective Effectmentioning
confidence: 99%
“…The cytotoxicity of selenite has been suggested to be due to the reaction with disulfide peptide or protein 15 17 18 . It is further linked to the protein aggregation disease, for example, cataract 19 20 21 . One hypothesis regarding the beginning of the cataract development suggests that selenium could oxidize the SH groups of ion transporters in the membrane that maintains calcium homeostasis 22 .…”
mentioning
confidence: 99%